SISTEM PENGANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) TERATAK BULUH KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2014 - Junita, Rahti; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Teratakbuluh village is one of in Siakhulu subdistrick Kampar districk. The analizy cosh and balances the Teratakbuluh village is less especially in 2014. Teratakbuluh village struggle to add the cosh so that the village can be using to all people is not except buerocracy. Teratakbuluh has many change the APBDes cause the Alokasi Dana Desa (ADD) is not enough to progress to all people in the village. So, Teratakbuluh village should many enter the cash village. In 2014, Teratakbuluh village has many money from Dana Perimbangan, Teratakbuluh village get from Siakhulu subdistrick and Kampar districk. The government Teratakbuluh village can be changed the rule of village (Peraturan Desa) which of UU Number 6 in 2014 about âVillageâ. So that, the rule of village can give to all people in the Teratakbuluh village to follow the rule especially APBDes. The methods to learn about APBDes in Teratakbuluh village is qualitative, and the key informan is all in village office. The writer give some problem about it, cause this is very interested to learn about APBDes in Teratakbuluh village, Siakhulu subdistrick Kampar districk. The writer conclude about APBDes Teratakbuluh still less to enough all people. The suggestion, Teratakbuluh village should the get cash village so that release the problem.Key words: The analizy APBDes, Teratakbuluh village, The planning theory